THE ROLE OF ADMINISTRATION MEETING TO INCREASE FAMILY ABILITY TO IMPROVE CHILDREN'S QUALITY - Darwadi Darwadi (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
AbstractThe problem in this study is the extent to which the quality of the children of the Family Hope Program (KPM) Family Hope Program (PKH) after the parents, especially the mother, received assistance at PKH, known as the Assistance of Family Capacity Building Meeting (P2K2). PKH is a program of the Republic of Indonesia government in breaking the poverty chain in Indonesia. P2K2 assistance itself is the implementation of Out of School Education (PLS) because in practice there is a process of education and training, transfer of non-formal knowledge and skills in the fields of family management, education, health, and economics. When PKH KPM gets knowledge and skills in these fields, it is hoped that there will be an influence on the quality of KPM PKH children with indicators set by the Ministry of Social Affairs of the Republic of Indonesia, namely: (1) Poor nutritional status for children under five (2) Increase food consumption energy and protein for children, (3) Increasing average length of schooling for children, (4) Increasing the average number of children's school participation, and (5) Reducing the number of working hours of children or the absence of working children. This study uses a qualitative method with a descriptive approach. Based on the results of the study, the P2K2 mentoring program run by PPKH Bandung which began in 2017 has been able to improve the quality of children in the form of increasing numbers of children who are absent from school more than 85% and toddlers or pregnant women who do not routinely assess their health at the service health facilities between 478% -687% from before the implementation of P2K2 counterpart program in 2016. Even so, the number of school drop out (DO) children and malnourished children also experienced a significant decline, from 48 children who DO in 2016 to 17 children in the year 2017, while children with malnutrition 0 (none) both in 2016 and 2017. Even so, the process of P2K2 Assistance will run less optimally during 2017 as the average number of implementation is 62%, the presence of KPM follows P2K2 assistance 79%, and the delivered curriculum is only about 61%. Thus the P2K2 mentoring program needs to continue to be developed because the results are good and to further maximize the implementation process.